The Methodological Quality of Economic Evaluation Studies in Obstetrics and Gynecology: A Systematic Review - Vijgen, Sylvia M.C.; Opmeer, Brent C.; Mol, Ben Willem J. (American Journal of Perinatology, 2013)
We evaluated the methodological quality of economic evaluation studies in the field of obstetrics and gynecology published in the last decade. A MEDLINE search was performed to find economic evaluation studies in obstetrics and gynecology from the years 1997 through 2009. We included full economic evaluation studies concerning tests or interventions in the field of obstetrics or gynecology. Each included study was evaluated by two reviewers using a quality checklist that was based on international guidelines for medical economic evaluation studies and a checklist used in a previous review. The mean number of quality criteria adhered to was 23 of 30 items, whereas five articles (3%) met all 30 criteria. Compliance was low for the description of the perspective (40%), the completeness of costs looking at the perspective (48%) or time horizon (48%), and reporting of quantities of resources (47%). Furthermore, if no discounting was applied, an explanation was infrequently given (14%). A comparison of study quality to that reported by Smith and Blackmore showed a considerable improvement in the following criteria: presentation perspective (from 19 to 40%), statement of primary outcome measure (from 72 to 81%), completeness costs looking at the time horizon (from 14 to 48%), the presentation of discount rates (from 10 to 54%), details of sensitivity analyses (from 21 to 61%), reporting incremental results (from 17 to 70%), and reporting a summary measure (from 57 to 74%). The quality of economic studies in obstetrics and gynecology has considerably improved in the last decade, but room for further improvement is present.
Keywords: obstetrics; gynecology; cost-effectiveness; economic evaluation; methodological quality